Factors That Influence On Compliance With Visits K1 To K4 In Pregnant Women In Parsoburuan Puskesmas, Habinsaran District Toba District In 2021 - Siti Nurmawan Sinaga (Institute of Computer Science (IOCS), 2021)
The problem of maternal mortality and morbidity in Indonesia is still a big problem. Utilization of Antenatal Care (ANC) services by a pregnant woman can be seen from the coverage of ANC services (K1 and K4). Based on the results of observations made by the authors of the Parsoburan Health Center, there are still pregnant women who do not check their pregnancies with antenatal care health workers regularly. This type of research is survey explanatory research. The purpose of this research is to analyze the factors that influence compliance with K1 to K4 visits for pregnant women at the Parsoburuan Public Health Center, Habinsaran District, Toba Regency in 2021. The population of this research is all pregnant women in Besitang District, Toba Regency, totaling 65 people and a sample of 60 people were taken by simple random sampling. Primary data was collected through interviews, and data analysis was performed using the chi square test and simple logistic regression test. The results of the chi square test and logistic regression test show that the variables age, knowledge, education, and affordability have a relationship and influence on ANC visits because the p value <0.05. This research is expected to provide input to the Toba District Health Office to improve antenatal care in Habinsaran District, provide information to increase pregnant women's knowledge, improve performance and pay more attention to the welfare of village midwives so they are willing to live and settle in the village..